Revisiting the colonial question in Latin America - Moraña, Mabel; Jáuregui, Carlos A. (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert, 2008)
From the configuration of Empire in the colonial period to the multiple facets of modern coloniality, this book offers a challenging approach to the developments and effects of imperial domination and neocolonial rule in Latin America. Thought of as a contribution to current debates on postcolonialism and covering an ample range of topics, geocultural fields, and historical scenarios, Revisiting the Colonial Question in Latin America provides indispensable materials to the study of the formation and representation of colonial and modern subjectivities, the role of historical accounts, cultural practices, and symbolic representation (literary writing, oral narratives, visual images, and artifacts) through which some of the parameters of colonized epistemologies become apparent to the European Other.
LEGAL PAGE -- CONTENTS -- REVISITING THE COLONIAL QUESTION IN LATIN AMERICA -- NOTES ON PRIMITIVE IMPERIAL ACCUMULATION. GINÉS DE SEPÚLVEDA, LAS CASAS, FERNÁNDEZ DE OVIEDO -- FORGOTTEN COLONIAL SUBJECTS -- SPANISH WOMEN IN FIRST NEW CHRONICLE AND GOOD GOVERNMENT: THE INTERSECTIONS OF CULTURE AND GENDER -- THE "INDIAN TUMULT" OF 1692 IN THE FOLDS OF BAROQUE CELEBRATIONS. HISTORIOGRAPHY, POPULAR SUBVERSION, AND CREOLE AGENCY IN COLONIAL MEXICO -- "WE'RE OUT THERE TAKING CARE OF FREEDOM": SLAVE RESISTANCE IN NINETEENTH-CENTURY BRAZIL -- HYBRIDITY, GENRE, RACE -- BETWEEN PROSPERO AND CALIBAN: COLONIALISM, POSTCOLONIALISM, AND INTER-IDENTITY -- COUNTERING CALIBAN. FERNÁNDEZ RETAMAR AND THE POSTCOLONIAL DEBATE -- RECONFIGURATIONS OF EMPIRE IN A WORLD-HEGEMONIC TRANSITION: THE 1898 SPANISH-CUBAN-AMERICAN-FILIPINO WAR -- THE RETROACTION OF THE POSTCOLONIAL: THE ANSWER OF THE REAL AND THE CARIBBEAN AS THING (AN ESSAY ON CRITICAL FICTION) -- ON FEMINISMS AND POSTCOLONIALISMS: REFLECTIONS SOUTH OF THE RIO GRANDE -- POSTCOLONIAL REPRESENTATIONS OF THE NEW WORLD (B)ORDER -- NOTE ON THE EDITORS AND CONTRIBUTORS.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2022. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Colonization -- History; Colonización -- Historia; América Latina -- Civilización.; España -- Colonias -- America -- Historia; Latin America -- Civilization; Spain -- Colonies -- America -- History; Libros electrónicos.